METTL3 counteracts premature aging via m6A-dependent stabilization of MIS12 mRNA. Issue 19 (9th October 2020) - Wu, Zeming; Shi, Yue; Lu, Mingming; Song, Moshi; Yu, Zihui; Wang, Jilu; Wang, Si; Ren, Jie; Yang, Yun-Gui; Liu, Guang-Hui; Zhang, Weiqi; Ci, Weimin; et al.
Abstract: N 6 -Methyladenosine (m 6 A) messenger RNA methylation is a well-known epitranscriptional regulatory mechanism affecting central biological processes, but its function in human cellular senescence remains uninvestigated. Here, we found that levels of both m 6 A RNA methylation and the methyltransferase METTL3 were reduced in prematurely senescent human mesenchymal stem cell (hMSC) models of progeroid syndromes. Transcriptional profiling of m 6 A modifications further identified MIS12, for which m 6 A modifications were reduced in both prematurely senescent hMSCs and METTL3-deficient hMSCs. Knockout of METTL3 accelerated hMSC senescence whereas overexpression of METTL3 rescued the senescent phenotypes. Mechanistically, loss of m 6 A modifications accelerated the turnover and decreased the expression of MIS12 mRNA while knockout of MIS12 accelerated cellular senescence. Furthermore, m 6 A reader IGF2BP2 was identified as a key player in recognizing and stabilizing m 6 A-modified MIS12 mRNA. Taken together, we discovered that METTL3 alleviates hMSC senescence through m 6 A modification-dependent stabilization of the MIS12 transcript, representing a novel epitranscriptional mechanism in premature stem cell senescence.